O estágio supervisionado como campo de pesquisa: discussões sobre gestão democrática e formação continuada no ambiente escolar - OLIVEIRA, Luiz Felipe Carvalho (2024)
This article is based on the experiences acquired during the supervised internship in the pedagogy course at the Federal University of Pará; it addresses the discussion related to the internship as a field for promoting research in school management and pedagogical coordination, and is a qualitative approach anchored in bibliographical research. The article also addresses the discussion of epistemology as a fundamental agent for the development of practical actions in both pedagogical coordination and school management, pointing out this correlation also called praxis within the dimension of work. In order to simplify reading, the work is divided into three topics, respectively: The internship as a field of research for school management and pedagogical coordination; the work of school management and pedagogical coordination in the school researched; the work of the pedagogical coordinator and continuing training: Challenges for working to value local culture.